1973
DOI: 10.1037/h0034948
|View full text |Cite
|
Sign up to set email alerts
|

Personal involvement, social judgment, and action.

Abstract: Relationships among the latitudes of acceptance, rejection, and noncommitment were investigated to develop indicators of ego involvement, using the owncategories method and the method of ordered alternatives. Degree of involvement was differentiated across attitude positions (extreme-moderate) and among persons taking the same position. Findings from five studies were that degree of involvement is (a) inversely related to fineness of discrimination in judging beliefs about one's reference group; ( 6) associate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
60
0
1

Year Published

1978
1978
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 140 publications
(63 citation statements)
references
References 25 publications
2
60
0
1
Order By: Relevance
“…Additionally, we found a significant correlation between personal involvement and conservation behavior which shows that conservation efforts increase with personal involvement in conservation issues. This finding supports previous studies, which have already shown that high personal involvement increases the likelihood of attitude-congruent behavior (e.g., Krosnick, 1988;Sherif, Kelly, Rodgers, Sarup, & Tittler, 1973).…”
Section: Discussionsupporting
confidence: 82%
“…Additionally, we found a significant correlation between personal involvement and conservation behavior which shows that conservation efforts increase with personal involvement in conservation issues. This finding supports previous studies, which have already shown that high personal involvement increases the likelihood of attitude-congruent behavior (e.g., Krosnick, 1988;Sherif, Kelly, Rodgers, Sarup, & Tittler, 1973).…”
Section: Discussionsupporting
confidence: 82%
“…A widely used measure of ego-involvement is the size of the latitude of rejection. Using this technique, researchers have demonstrated greater resistance to change of ego-involving attitudes (Halverson & Pallak, 1978;Sherif & Sherif, 1967;Sherif, Sherif, & Nebergall, 1965), and their better predictive validity (Budd & Spencer, 1984;Fazio & Zanna, 1978a;Sherif, Kelly, Rogers, Sarup, & Tittler, 1973). Small to moderate correlations were found with certainty (Fazio & Zanna, 1978a) and attitude accessibility (Fazio, Herr, & Olney, 1984).…”
Section: Ego-involvementmentioning
confidence: 95%
“…To the extent that either prerequisite is not present, the predictive power of the construct will be diminished. Support for the concept of self-or vested interest in political research can be traced to the pioneering efforts of Muzafir Sherif in his work on ego involvement (e.g., Sherif & Cantril, 1947;Sherif & Hovland, 1961;Sherif, Kelly, Rodgers, Sarup, & Tittler, 1973). Sherif, Sherif, and Nebergall (1965) examined involvement in political elections and found that highly ego-involved Preparation of this research was facilitated by a grant from the National Institute on Drug Abuse (R01 DA 12578-01) for which we are most grateful.…”
mentioning
confidence: 99%